Gravel and hawk : poems - Norwood, Nick, 1962- (Hollis Summers Poetry Prize., 2012)
Gravel and Hawk dwells on the physical and cultural landscapes of the Texarkana border region, an area of stark natural beauty and even starker manifestations of its human habitation: oil derricks and pump jacks, logging trucks, chicken houses, come-to-Jesus billboards, and greasy catfish joints, a patchwork of dying farm towns and ragtag municipalities laced together by county roads, state highways, and that treacherous, rust-hued slurry known as the Red River. Gravel and Hawk charts the emotional landscape of a single extended family, its history of loss and gain, and, especially, its encou.